Design and practice of Guiyang open government data platform - Mingfeng HUANG; Jun LIU; Jianbo JING (Dianxin kexue)
As the social public resources,the value and function of government data has become a global consensus,but the construction of our local open government data platforms is still in a preliminary stage.Taking the Guiyang open government data platform as an example,the design and construction scheme of open government data platform was introduced from various modes,general framework,potential data acquisition mode,data quality management and metadata construction.The meaningful reference for the construction of our local open government data platform was provided.